A Multivariate Study on the Role of Palm Print Features for Estimating Age, Gender, Lineage and Profession - Gautam kumar; Khalida Nazeer; Namrata singh; Asim ameen; Roomi parveen; Ekta singh yadav (Universitas Airlangga, 2025)
Palmprints, just like fingerprints are unique and permanent and thus have the potential to be used as biometric markers. Palmprints holds more potential for identification markers because of its larger surface area but many of its features are not yet explored. This review article presents a narrative literature review of studies published between 1987 and 2025 to evaluate the role of palmprint features in estimating age, gender, lineage, and occupation. Relevant research articles were examined to assess the influence of biological, hereditary, and occupational factors on palmar ridge patterns, crease morphology, and ridge density. Relevant research articles were examined to assess the influence of biological, hereditary, and occupational factors on palmar ridge patterns, crease morphology, and ridge density. The review also analyses advancements in automated palmprint identification systems and modern deep-learning approaches such as CNN, ResNet-50, DeepPalmNet, and CAM for feature extraction and demographic prediction. The studies have revealed that aging affects ridge clarity and crease prominence, while ridge density and crease pattern differs significantly between males and females. Occupations involving manual labor often leave permanent marks on palms, which can act as indicators during forensic examinations. Additionally, certain hereditary features of palmar creases have been found to be consistent within ethnic or familial groups, providing insights into ancestry. The integration of palmprint analytics with national biometric systems such as AFIS and APIS has strengthened forensic applications. Overall, this review emphasizes the need for more population-based studies and the development of standardized palmprint databases to enhance the forensic utility of palmprints in personal identification.